Designing Journeys Application Interface to Improve Indonesian UMKM Accessibility with a User Centered Design Approach - Putra, Anak Agung Adi Wiryya; Putra, I Gede Elang Perdana Dwi; Sudharma, Made Wahyu; Putra, I Made Dharma (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
This study examines the application of UI/UX principles to the